Implementasi Aplikasi Tiktok Dalam Desain Pesan Kreatif Remaja Di Kota Parepare - Mahfud, Muh. Mahfud Idrus (Communication and Islamic Broadcasting Studies IAIN Parepare, 2024)
The rise of the current technological era, people need guidance in wise use of social media, also the presence of this Tiktok application as a new media will have a good impact on society. The phenomenon of using the Tiktok application in the city of Parepare, especially teenagers with various kinds of creativity and delivering messages through positive youth content through Tiktok. This tiktok application is also an application that is favored and liked by teenagers to develop their creativity, the intensity of teenagers in using the Tiktok application is increasing. So that researchers believe the Tiktok application is an interesting problem to research. Based on the object of research and the problems studied, this research is a field research, which is a research that is carried out systematically by collecting data from the field. content is necessary. This will give their own interest to the content of teenagers in the Tiktok application they produce. It needs an idea, because in the content there needs to be something that will make certain characteristics different from others.